Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan Di Restoran Oplet Ijo Kota Palembang - Michelle Gouw; Megawati Megawati (MDP Student Conference, 2026)
This study aims to analyze the influence of product quality on customer satisfaction at Oplet Ijo Restaurant, Palembang. Using an associative quantitative approach, data were collected through questionnaires from 347 respondents selected using purposive sampling techniques with the criteria of having visited at least twice. Data analysis was performed using simple linear regression with SPSS 26 software. The results showed that product quality has a positive and significant influence on customer satisfaction, as evidenced by a tcount value of 14,662 > ttable 1,967 and a significance level of 0,000 < 0.05. The coefficient of determination (Adjusted R2) of 0,643 indicates that the product quality variable explains 64,3% of the variation in customer satisfaction. This indicates that improvements in flavor, freshness, appearance, and menu innovation indicators at Oplet Ijo Restaurant significantly increase customer satisfaction.